Assessment of glycemic control practices among patients with diabetes at Khadimpara Hospital - Arefin, Nusrat; Shaon, Rezaul Karim; Panthadas, Anamika; Paul, Kishore Kumar; Shuvra, Shantanu Roy; Parag, Deb Dulal Dey (International Journal of Research in Medical Sciences, 2025)
Background: Diabetes mellitus, a chronic condition characterized by elevated blood glucose levels due to insufficient or ineffective insulin, affects 537 million adults globally. Effective glycemic control is essential for preventing complications in patients with diabetes mellitus. This study aimed to assess glycemic control practices among diabetic patients attending Khadimpara Hospital, Sylhet. Methods: This quantitative, cross-sectional study was conducted at Khadimpara 31-bed hospital, Sylhet, Bangladesh, from July to December 2024. A total of 221 patients diagnosed with diabetes mellitus (DM), aged 35 years or older, attending Khadimpara Hospital in Sylhet, were included in the study. Results: The mean age of participants was 54.61±10.89 years, with the majority aged 51-60 years (34.4%). Females slightly outnumbered males (51.1% versus 48.9%). Nearly half (47.5%) had a normal BMI, while 34.8% were underweight. Most participants (73.8%) had a family history of diabetes, and the median duration of diabetes was five years (IQR 3-7). Regarding treatment, 54.3% had been on anti-diabetic medications for 1-5 years, and 86.9% reported diabetes-related complications. The most common management strategy (83.26%) was a combination of drug therapy, diet, and exercise. A statistically significant association was found between management approach and diabetes control (p=0.002), with combined interventions yielding the highest success rate (70.1%). Conclusions: This study highlighted that most patients effectively manage diabetes mellitus through a combination of drug therapy, physical exercise, and diet control, with significant correlations observed between glycemic control and factors like gender, occupation, and family history.